Initial Experience With Satisfactory-Unsatisfactory Grading in Accounting Courses. - Carpenter, Charles C.; Strawser, Robert H. (The Accounting Review, 1971)
Abstract Recently a study was conducted to determine some of the effects of accounting majors who take courses in their major field of study on the satisfactory-unsatisfactory grading basis. One by-product of the option originally intended to allow students a more free-ranging choice of courses and reduce some of the tensions arising out of the emphasis upon grade averages is that students majoring in accounting are scheduling courses in their major field on the satisfactory-unsatisfactory basis. This may be reducing some of the tensions arising out of emphasis upon grade averages, but it does not seem to encourage students to select courses outside their major academic areas. The study indicates that on average better students in terms of prior academic performance are choosing the satisfactory-unsatisfactory option. On average, these students did not perform as well as those students on the conventional grading system. Also, they did not perform to the full extent of their capabilities indicated by their previous grade-point averages, both overall and in accounting.